Matriks Leslie dan Aplikasinya pada Pemodelan Jumlah Populasi Perempuan di Sumatera Barat - Mayang Sugara; Arnellis Arnellis (UNIVERSITAS NEGERI PADANG, 2021)
The Leslie matrix is a demographic method for calculating the number and growth rate of a population. This method was applied to determine the female population in West Sumatera. The growth of the female population in West Sumatera can affect the population because it has the nature to breed. Based on the Central Statistics Agency for West Sumatera in 2020, it was recorded the population of West Sumatera consisted of 5,534,472 people. This data has increased compared to 2010 amounting to 687,563 people. This study aims to prove the theorem of the characteristics of the Leslie matrix and application the number and rate of the female population in West Sumatera on next two years. This research is an applied research with secondary data obtained through the website of the Central Statistics Agency (BPS) and the West Sumatera Health Service. The research was conducted by proving the characteristics of the Leslie matrix and its use with a matrix size of